Disruptive Innovation - Dastur, Percy Agreras; SAWANT, SANDEEP (Mumbai: Embassy Books, 2012)
Although the term is now a much discussed one in business circles the concept of Disruptive Innovations has always been a part of the business environment. It's a term to explain an unexpected improvement - by way of a product or a service - that creates new values and markets, thus enabling firms in the same industry to compete against each other, and succeed. Thomas Edison's discovery of the light bulb was an excellent example of this phenomenon. This book shows how Disruptive Innovation can be used to your advantage in today's business environment to stay ahead of the game and lead the way for others. Key Selling Points : Helps understand the concept of Disruptive Innovation through real-life successful cases. Explains the applications of Disruptive Innovation in different types of markets around the world. Advises leaders about the appropriate method of tackling Disruptive Innovation.
Keywords: BAWA, BALJIT